Factors That Influence Brand Loyalty on Scarlett Whitening Products - Theresia Suryadi; Margaretha Pink Berlianto (Universitas Pelita Harapan, 2024)
This research aims to analyze the factors that influence brand loyalty for Scarlett Whitening products. The population of this study was domiciled people in Jakarta, Bogor, Depok, Tangerang and Bekasi who had used Scarlett Whitening products using a purposive sampling technique and distributing questionnaires to a total of 265 respondents. Data was analyzed using PLS-SEM. The results showed that advertising spending, attitudes towards advertising, and value congruity have a positive effect on brand identification and brand image. Brand identification has a positive effect on brand image, brand engagement, brand love and brand loyalty. Brand image has a positive effect on brand love. Brand engagement and brand love have a positive effect on brand loyalty.